The Use Of Green Star Certificates As A Marketing Tool On Hotel Websites - Ozdipciner, Nuray Selma; Ceylan, Seher; Soydas, Muhammet Emin (European Scientific Journal, ESJ, 2016)
Environmental sensitivity is one of the main expectations of customers. Increase in the awareness of customers causes companies to become more sensitive. Green star certification for hotels is one of the many applications of this understanding. In this study, websites of all green star hotels in Turkey were evaluated for content. Furthermore, this study tried to find out the usefulness of green star certification as a marketing tool. The main aim of the study is to research the visibility of green star certificates on websites in terms of attracting potential environment sensitive customers. The data obtained was evaluated by SPSS statistical programme, and frequency tables and cross tables (according to company type and class) were drawn out. Based on the findings of this study, hotel establishments do not use green star certificates as a marketing tool on their websites. It was suggested that hotels should use green star certificates more efficiently by putting them on their websites so as to attract potential environment sensitive customers.